2011
DOI: 10.1200/jop.2011.000260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Electronic Health Record on the Culture of an Outpatient Medical Oncology Practice in a Four-Hospital Integrated Health Care System: 5-Year Experience

Abstract: The electronic health record (EHR) was adopted into the NorthShore University HealthSystem, a four-hospital integrated health system located in suburban Chicago, in 2003. By 2005, all chemotherapy and medicine order entry was conducted through the EHR, completing the incorporation of a fully paperless EHR in our hospital-based oncology practice in both the inpatient and outpatient settings. The use of the EHR has dramatically changed our practice environment by improving efficiency, patient safety, research pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
(5 reference statements)
1
12
0
Order By: Relevance
“…This result is congruent with the positive results of other studies that have assessed some EMR functions for cancer care, mainly in improving documentation and standardising procedures in parts of the care process, such as order entry systems, to support the chemotherapy process in medical oncology (Adelson et al, 2014;Brockstein et al, 2011;Harshberger et al, 2011;Kukreti et al, 2014;Levy et al, 2011;Meisenberg et al,2014;Pirnejad et al, 2013) and electronic checklists (record and verify software) in radiation oncology (Albuquerque et al, 2011;Chua et al, 2010;Goldwein, 2011;Kirkpatrick et al, 2013). The users' attitudes, as measured by both the survey and the interviews, were quite positive in the post-period, and the new EMR was considered better than the former system.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is congruent with the positive results of other studies that have assessed some EMR functions for cancer care, mainly in improving documentation and standardising procedures in parts of the care process, such as order entry systems, to support the chemotherapy process in medical oncology (Adelson et al, 2014;Brockstein et al, 2011;Harshberger et al, 2011;Kukreti et al, 2014;Levy et al, 2011;Meisenberg et al,2014;Pirnejad et al, 2013) and electronic checklists (record and verify software) in radiation oncology (Albuquerque et al, 2011;Chua et al, 2010;Goldwein, 2011;Kirkpatrick et al, 2013). The users' attitudes, as measured by both the survey and the interviews, were quite positive in the post-period, and the new EMR was considered better than the former system.…”
Section: Discussionsupporting
confidence: 87%
“…The literature nevertheless reports several positive results. For instance, in medical oncology, benefits have been demonstrated in terms of compliance with guidelines (Adelson et al, 2014;Levy et al, 2011;Meisenberg, Wright, & Brady-Copertino, 2014), documentation completeness Harshberger et al, 2011;Levy et al, 2011), fewer problematic orders (Adelson et al, 2014;Brockstein et al, 2011;Kukreti, Cosby, Cheung, & Lankshear, 2014;Meisenberg et al, 2014), improved multidisciplinary team communication (Levy et al, 2011), lighter workloads (Kukreti et al, 2014;Pirnejad, Gao, Reddingius, Rijnevevld, & Bal, 2013) and faster turnaround times (Pirnejad et al, 2013). In radiation oncology, benefits have also been reported in terms of better documentation (Albuquerque, Miller, & Roeske, 2011;Goldwein, 2011;Kirkpatrick et al, 2013), real-time generation of outcome data (Chua et al, 2010), standardised procedures (Albuquerque et al, 2011) and the number of times that physicians were called to the treatment unit (Albuquerque et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies describe the methods used for implementing a cpoe system for chemotherapy 6,14,19,28 . Harshberger et al 29 reported improved user satisfaction and better completeness of chemotherapy orders and documentation after a cpoe system was implemented to replace paper-based charts at a large multi-site teaching hospital, and Brockstein et al 30 described the impact of the cpoe implementation at the same institution on documentation, communication, operations, quality improvement, and research. At a large Dutch teaching hospital, Pirnejad et al 31 found that a user requirement-driven and process-oriented cpoe system development process and proximity of the development site to the implementation site resulted in a preference by the chemotherapy and hematology clinicians for a home-grown cpoe system over a commercially available hospital-wide cpoe system.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the three medical oncology practices began using Epic in the ambulatory setting in 2011 and began using Beacon for CPOE of chemotherapy in January 2012. Use of the Beacon system has been described previously, most comprehensively by Brockstein et al 9 and Harshberger et al 10 Each regimen has to be built to include chemotherapy drugs, nursing instructions, and supportive care medications and fluids as appropriate. The goal was to ensure that the content would be identical to the preprinted order, even if the display was not.…”
Section: Cpoementioning
confidence: 99%